The Effect Of Giving The Thought Stoping Method On The Level Of Anxiety Of Pregnant Women In Ujung Loe District - Nurlina; Andi Resky Ika Fitri; Asri (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Background: Based on WHO data (World Health Organization) there are about 13% of pregnant women who experience anxiety disorders. In developing countries, the percentage can even reach 19.8%. Pregnant women who experience anxiety continuously will have an impact on the health of themselves and their fetuses, such as babies born with low birth weight (LBW), preterm birth, spontaneous chromosomal abortion, low APGAR scores for the occurrence of hyperemesis gravidarium, preeclampsia, and eclampsia. Objective: To determine the effect of the thought-stopping method on the anxiety level of pregnant women in Ujung Loe District in 2022. Methods: This study used a quasi-experimental research design with a quasi-experimental approach; a non-randomized re-experimental design (non-randomized pretest-posttest with control group design) was used. The sample size in this study was 40 pregnant women, of which 20 pregnant women were in the experimental group, and 20 pregnant people were in the control group. The sampling technique used is consecutive sampling. The thought-stopping method was given 2 times in 2 meetings for a week with a duration of 30 minutes for each 1 meeting. Data analysis in this study used an unpaired T-test. Results: The results of the analysis using the unpaired T statistical test obtained p value = 0.000, which means Ho is rejected, and Ha is accepted, or there is an effect of giving the thought stoping method on the anxiety level of pregnant women in Ujung Loe District in 2022. Conclusion: Pregnant women in the experimental (intervention) group experienced a decrease in anxiety, which means that there was an effect of giving the thought stopping method on the anxiety level of pregnant women in Ujung Loe District in 2022.